1995
DOI: 10.1007/bf02246080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of nicotine on a fixed rate and a subject-paced version of the rapid information processing task

Abstract: In a modified "subject-paced" rather than fixed rate version of a rapid information processing (RIP) task, the presentation rate of the stimuli is continuously adapted to the individual performance level. Thus, this modified task version probably assesses a continuous "speed function" rather than mere "vigilance". In order to compare the two task versions more directly, we carried out a study which assessed the effects of a regular nicotine cigarette and the nearly nicotine-free cigarette NEXT on both task ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…Past demonstrations of stimulant-induced cognitive improvements using the RIP task involved cholinergic stimulants, such as nicotine (e.g., Baldinger et al, 1995) and the non-specific stimulant, caffeine (Hasenfratz et al, 1993). The present results extend the previous findings by showing that similar enhancing effects on information processing can be produced by a dopaminergic-acting stimulant drug.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Past demonstrations of stimulant-induced cognitive improvements using the RIP task involved cholinergic stimulants, such as nicotine (e.g., Baldinger et al, 1995) and the non-specific stimulant, caffeine (Hasenfratz et al, 1993). The present results extend the previous findings by showing that similar enhancing effects on information processing can be produced by a dopaminergic-acting stimulant drug.…”
Section: Discussionsupporting
confidence: 85%
“…Studies of RIP task performance show increased information processing capacity following the administration of cholinergic stimulants, such as nicotine (e.g., Baldinger et al, 1995;Hasenfratz and Battig, 1994) and non-specific stimulants, such as caffeine (Hasenfratz et al, 1993). Moreover, these improvements do not simply reflect relief from temporary withdrawal-induced performance deficits, but rather represent actual, above-baseline facilitation of information processing.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research indicates that non-nicotine components of smoking contribute to nicotine dependence (see Robinson et al 2000 andRose 2005 for reviews). As several studies have consistently shown, smoking denicotinized cigarettes provides relief from craving and withdrawal symptoms in abstinent smokers (Gross et al 1997;Pickworth et al 1999;Westman et al 1996), but does not reverse the cognitive deficits associated with abstinence (Baldinger et al 1995). Related research assessing prepulse inhibition (PPI) of startle in overnight abstinent smokers found that smokers did not exhibit significantly lower PPI when abstinent overnight compared to findings on an ad libitum smoking day.…”
Section: Discussionmentioning
confidence: 99%
“…It requires sustained attention but also has a moderate working memory load. Nicotine has been found to decrease reaction times and improve correct detections on this task (Foulds 1996, Warburton and Mancuso 1998, Baldinger et al 1995, Revell 1988. These findings are unlikely to reflect the reversal of a withdrawal-induced deficit in performance in nicotine-dependant smokers as they have also been observed in non-abstinent smokers (Warburton and Arnall 1994) and non-smokers (Wesnes & Revell, 1984).…”
Section: Introductionmentioning
confidence: 92%